2017
DOI: 10.3389/fmicb.2017.00948
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Compositional Stability of Bacterial Metacommunities in Response to Salinity Changes

Abstract: Disturbances and environmental change are important factors determining the diversity, composition, and functioning of communities. However, knowledge about how natural bacterial communities are affected by such perturbations is still sparse. We performed a whole ecosystem manipulation experiment with freshwater rock pools where we applied salinity disturbances of different intensities. The aim was to test how the compositional and functional resistance and resilience of bacterial communities, alpha- and beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 70 publications
5
24
2
Order By: Relevance
“…In addition, our results indicate a larger change in community composition for the 35 °C than for the 25 °C treatment. This is in agreement with results from previous studies using other types of disturbances, which showed, for example, that bacterial community composition changed gradually with increasing intensities and frequencies of a salinity disturbance 13,32 or increasing concentration of a pollutant 14 . Moreover, the results clearly show a lack of compositional recovery in response to the applied temperature disturbances.…”
Section: Experiments 1: Effect Of Repeated Temperature Disturbances Atsupporting
confidence: 93%
“…In addition, our results indicate a larger change in community composition for the 35 °C than for the 25 °C treatment. This is in agreement with results from previous studies using other types of disturbances, which showed, for example, that bacterial community composition changed gradually with increasing intensities and frequencies of a salinity disturbance 13,32 or increasing concentration of a pollutant 14 . Moreover, the results clearly show a lack of compositional recovery in response to the applied temperature disturbances.…”
Section: Experiments 1: Effect Of Repeated Temperature Disturbances Atsupporting
confidence: 93%
“…We had assumed that FYM application would have resulted in a higher functional diversity due to the more varied range of substrates and an increased species richness in this treatment. This implies that there is a greater amount of microbial functional redundancy ( Taketani et al, 2015 ; Berga et al, 2017 ) in the FYM treated strip. Future work should determine whether or not this is the case through metagenomics as well as microbial isolate sequencing efforts.…”
Section: Discussionmentioning
confidence: 99%
“…The development of a more mechanistic picture is hindered for several reasons, such as difficulties in identifying the relative role of stochastic and deterministic processes in shaping microbial communities [5][6][7] , and the pervasiveness of functional redundancy 8,9 and of priority effects 10 . In addition, it is often difficult to identify which functions to assess.…”
mentioning
confidence: 99%
“…An important step forward comes from manipulative experiments in natural environments, which have identified variables such as pH 12 , salinity 8 , sources of energy 13 , the number of species 14 and environmental complexity 4 as key players in the relationship between bacterial community structure and functioning. Improved control can be obtained by domesticating communities surveyed from natural environments by growing them in a synthetic (albeit complex) environment, and quantifying their functioning under such controlled conditions 15,16 .…”
mentioning
confidence: 99%